Risk Factors for Ischemic Cerebral Stroke in German and Polish population - Bejer, Agnieszka; Ax, Anna Maria; Dockweiler, Urlich; Grzegorczyk, Joanna; Lenart-Domka, Ewa; Kwolek, Andrzej; Magoń, Grzegorz; Pop, Teresa; Przysada, Grzegorz (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Introduction. As research shows, the prevalence of risk factors is high. Therefore, the main goals of the Helsingborg Declaration is to reduce, by 2015, the incidence of risk factors for stroke, particularly hypertension and smoking. Community-based actions aiming at reduction, detecting and management of risk factors for stroke should be available. Recommendations also include promotion of healthy lifestyles, and if there is a necessity - appropriate drug treatment should be applied. At the same time, all patients ‘who suffered stroke or a TIA should be examined for the causes of those disorders. Later, those individuals should be provided with secondary preventive measures. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study aimed at making a comparison of the prevalence of risk factors for ischemic stroke in German and Polish populations. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Material and method. The study group consisted of 123 individuals, including 58 Polish and 65 German people. In the German population, the majority (708) of the participants were males, whereas the Polish population featured identical proportion of males and females (50% each). <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Results. Risk factors occur with similar frequency in females and males in both populations. Only the Polish group showed two statistically significant differences - atrial fibrillation is more likely in females, and tobacco smoking in males. The level of education has barely any impact on the frequency of risk factors incidence. There is only one exception in the Polish group - hypothyroidism is more likely in less educated people. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusions. Effort should be made to promote no smoking, and treatment of nicotine dependence, as this is one of the major risk factors for stroke in young males. Poles should be encouraged to take up physical activity, while Germans would benefit from a cholesterol lowering diet, due to the frequency of respective factors in both groups. Of notice is the coexistence of several (most often 3) risk factors in both German and Polish patients. The knowledge of all those factors can benefit the effectiveness of preventive measures.